Letter from Lily Yeats, [1907-11-07] - http://id.worldcat.org/fast/202679 (1907)
A handwritten letter to an unnamed customer from Lily Yeats in which she states "I have just posted to you Katherine Tynan's poems". She also encloses two book- markers "painted by the girls. My sister teaches them painting & drawing."